2003
DOI: 10.1093/toxsci/kfh023
|View full text |Cite
|
Sign up to set email alerts
|

Role of Aryl Hydrocarbon Receptor in Mesencephalic Circulation Failure and Apoptosis in Zebrafish Embryos Exposed to 2,3,7,8-Tetrachlorodibenzo-p-Dioxin

Abstract: 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) is a persistent and potent developmental toxicant in various animals, with developing fish being the most sensitive organisms. Although the expression of aryl hydrocarbon receptor (AHR) as well as the partner molecule, AHR nuclear translocator (ARNT) in the brain has been reported, the effect of TCDD on the brain remains to be clarified in detail. Previously, we reported local circulation failure and apoptosis in dorsal midbrain caused by TCDD in developing zebrafish.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 37 publications
0
66
0
Order By: Relevance
“…Fish typically have four AHR genes, products of a tandem gene duplication ( AHR1 and AHR2 ) and paralogs of each of these (designated “a” and “b”), the result of a whole‐genome duplication at the base of the teleost lineage, after its divergence from the lineage leading to tetrapods (Hahn et al., 2006, 2017). The relative roles of each AHR are not yet fully understood, but the AHR2 paralogs appear to mediate many of the toxic and adaptive responses to DLCs and some PAHs (Antkiewicz, Peterson, & Heideman, 2006; Billiard et al., 2006; Clark et al., 2010; Dong, Teraoka, Tsujimoto, Stegeman, & Hiraga, 2004; Goodale et al., 2012; Incardona et al., 2006; Jönsson et al., 2007; Lanham, Prasch, Weina, Peterson, & Heideman, 2011; Prasch et al., 2003; Waits & Nebert, 2011). For some chemicals, however, responses may be mediated by AHR1 (Goodale et al., 2012; Incardona et al., 2006).…”
Section: Ahr Pathwaymentioning
confidence: 99%
“…Fish typically have four AHR genes, products of a tandem gene duplication ( AHR1 and AHR2 ) and paralogs of each of these (designated “a” and “b”), the result of a whole‐genome duplication at the base of the teleost lineage, after its divergence from the lineage leading to tetrapods (Hahn et al., 2006, 2017). The relative roles of each AHR are not yet fully understood, but the AHR2 paralogs appear to mediate many of the toxic and adaptive responses to DLCs and some PAHs (Antkiewicz, Peterson, & Heideman, 2006; Billiard et al., 2006; Clark et al., 2010; Dong, Teraoka, Tsujimoto, Stegeman, & Hiraga, 2004; Goodale et al., 2012; Incardona et al., 2006; Jönsson et al., 2007; Lanham, Prasch, Weina, Peterson, & Heideman, 2011; Prasch et al., 2003; Waits & Nebert, 2011). For some chemicals, however, responses may be mediated by AHR1 (Goodale et al., 2012; Incardona et al., 2006).…”
Section: Ahr Pathwaymentioning
confidence: 99%
“…In separate experiments, fish have provided evidence that the vascular endothelium is also a sensitive target for TCDD toxicity, and this may prove important with regards to the human health effects of TCDD. In fish TCDD elicits increased vascular permeability, which in lake trout manifests as yolk sac edema, and in zebrafish as extravascular accumulation of serum proteins in mesencephalic brain tis-sues (Guiney et al, 2000;Dong et al, 2004). Although the precise nature of this microvascular leakage remains to be determined, decreased cardiac output, increased endothelial vacuolation (Guiney et al, 2000), disruption of peripheral vascular beds (Henry et al, 1997) and/or disruption of angiogenic signaling (Bello et al, 2004) have been suggested.…”
Section: Effects Of Tcdd Exposure On Development Ahr In Developmentmentioning
confidence: 99%
“…Knockout studies show that ligand-activated aryl hydrocarbon receptor (AHR) largely determines the induction of mammalian CYP1As and CYP1B1 (e.g., Shimada et al, 2002). AHR also regulates CYP1As in non-mammalian vertebrates; knock-down of AHR2 in zebrafish (Danio rerio) embryos abolishes induction of the single CYP1A by the potent AHR agonist 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) (Prasch et al, 2003;Dong et al, 2004). TCDD also induces zebrafish CYP1B1 (Handley-Goldstone et al 2005), presumably via the AHR.…”
Section: Introductionmentioning
confidence: 99%
“…TCDD also induces zebrafish CYP1B1 (Handley-Goldstone et al 2005), presumably via the AHR. Knockout and knockdown studies show that AHRs mediate TCDD toxicity in mammals and fish (Fernandez-Salguero et al, 1996;Prasch et al, 2003;Dong et al, 2004).…”
Section: Introductionmentioning
confidence: 99%